Efficacy Comparison of Nitazoxanide Combined with Lactulose versus Lactulose Monotherapy in Managing Overt Hepatic Encephalopathy - Janjua, Taimoor Hafeez; Ali, Amanat; Ahmed, Sameer; Shakir, Sabeen; Rashid, Zunera; Irfan, Asma (Journal of Rawalpindi Medical College, 2025)
Objective: To evaluate the efficacy of combining Nitazoxanide with lactulose compared to lactulose alone in the treatment of overt hepatic encephalopathy. Methods: This Comparative Cross-sectional Study was conducted at the department of Gastroenterology and Hepatology, Pakistan Institute of Medical Sciences, Islamabad from July 2019 to December 2019. In this study, 150 cirrhotic patients with overt hepatic encephalopathy were randomized into two groups: one receiving Nitazoxanide plus Lactulose (Group A) and the other receiving Lactulose alone (Group B). Patient demographics, aetiology of cirrhosis, MELD score, and efficacy of treatment were assessed. Statistical analysis was conducted to compare outcomes between the two groups. Results: A total of 150 patients, with a mean age of 44.08 ± 11.31 years were enrolled. Hepatitis C was the predominant aetiology in 81 patients (54%). The mean MELD score was 23.24 in Group A and 22.36 in Group B. Upon admission, 20 patients (13.3%) presented with grade 2 hepatic encephalopathy (HE), while 70 patients (46.6%) had grade 4 HE. The duration of hospital stay showed statistical significance in both groups (p < 0.001). Furthermore, a significant difference in drug efficacy was observed between the two groups (p < 0.005). Conclusion: In conclusion, our study suggests that combining Nitazoxanide with Lactulose yields superior efficacy compared to Lactulose alone in managing overt hepatic encephalopathy among cirrhotic patients. Keywords: Comparison, Efficacy, Hepatic encephalopathy, Lactulose, Management, Nitazoxanide, Treatment.